2002
DOI: 10.1161/hc0402.102663
|View full text |Cite
|
Sign up to set email alerts
|

Electroanatomic Substrate of Idiopathic Left Ventricular Tachycardia

Abstract: Background-An abnormal potential (retroPP) from the left posterior Purkinje network has been demonstrated during sinus rhythm (SR) in some patients with idiopathic left ventricular tachycardia (ILVT). We hypothesized that this potential can specifically be identified and be a critical substrate for ILVT. Methods and Results-In 9 patients with ILVT and 6 control patients who underwent mapping of the left ventricle during SR using 3-dimensional electroanatomic mapping, an area with retroPP was found within the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(61 citation statements)
references
References 24 publications
2
56
2
1
Order By: Relevance
“…The left posterior fascicular Purkinje fiber-related reentrant VT is one of the most popular idiopathic VTs [1][2][3][4][5] . This VT is verapamil-sensitive and its QRS morphology is a RBBB configuration with left axis deviation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The left posterior fascicular Purkinje fiber-related reentrant VT is one of the most popular idiopathic VTs [1][2][3][4][5] . This VT is verapamil-sensitive and its QRS morphology is a RBBB configuration with left axis deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Ouyang et al has reported that the earliest diastolic potential during the sinus rhythm detected around the left posterior fascicle can be substrate for idiopathic left ventricular tachycardia with a RBBB configuration and left-axis deviation 5 . They called that potential as retro PP, because these abnormal potentials may represent a retrograde Purkinje activation with slow conduction over a Purkinje-Purkinje or Purkinjeventricular-Purkinje connection attributable to unidirectional block 5 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations